Economic Plants of Tripura State IX. Plants Yielding Tannins - Deb, D. B. (Indian Forester, 1981)
The present paper entitled ’Economic plants of Tripura State IX, Plants yielding tannins’ presents a survey of the plants of Tripura State, which contain a fairly good percentage of Tannins, worthy of consideration for commercial exploitation.